Multiple Mini Incision Technique for Sural Nerve Harvest: When to Add a Fibular Incision Based on a New Surgical Classification - Raveendran, Sreekanth; Thomas, Binu Prathap (Journal of Hand and Microsurgery, 2023)
Sural nerve is the most common nerve used as a source for nerve grafting. Open harvest with longitudinal incisions produces unsightly scars, and this have led to development of less invasive techniques using endoscopes, nerve stripper, and mini-incisions. Several anatomical classifications have also been proposed due to the variations in the anatomy of the sural nerve. A simple and practical surgicoanatomical classification of the sural nerve based on which we have refined our minimal access technique, the multiple mini-incision technique for sural nerve harvest is proposed. In this technique, the incisions required for harvest of the sural nerve are standardized and predictable. A fibular incision is required when the sural nerve has major contribution from the common peroneal nerve. We have found this a simpler and reliable technique of harvest of sural nerve in nerve reconstructive surgery.
Keywords: brachial plexus; hand injury; nerve anastomosis; sural nerve harvest; sural nerve; nerve grafting